In vivo Bioluminescence Imaging of Burkholderia mallei Respiratory Infection and Treatment in the Mouse Model - Massey, Shane; Johnston, Katie; Mott, Tiffany M.; Judy, Barbara M.; Kvitko, Brian H.; Schweizer, Herbert P.; Estes, D M.; Torres, Alfredo G. (Frontiers in Microbiology, 2011)
Bioluminescent imaging (BLI) technology is a powerful tool for monitoring infectious disease progression and treatment approaches. BLI is particularly useful for tracking fastidious intracellular pathogens that might be difficult to recover from certain organs. Burkholderia mallei, the causative agent of glanders, is a facultative intracellular pathogen and has been classified by the CDC as a Category B select agent due to its highly infectious nature and potential use as a biological weapon. Very little is known regarding pathogenesis or treatment of glanders. We investigated the use of bioluminescent reporter constructs to monitor the dynamics of infection as well as the efficacy of therapeutics for B. mallei in real time. A stable luminescent reporter B. mallei strain was created using the pUTmini-Tn5::luxKm2 plasmid and used to monitor glanders in the BALB/c murine model. Mice were infected via the intranasal route with 5x103 bacteria and monitored by BLI at 24, 48 and 72 h. We verified that our reporter construct maintained similar virulence and growth kinetics compared to wild-type B. mallei and confirmed that it maintains luminescent stability in the presence or absence of antibiotic selection. The luminescent signal was initially seen in the lungs, and progressed to the liver and spleen over the course of infection. We demonstrated that antibiotic treatment 24 h post-infection resulted in reduction of bioluminescence that can be attributed to decreased bacterial burden in target organs. These findings suggest that BLI can be used to monitor disease progression and efficacy of therapeutics during glanders infections. Finally, we report an alternative method to mini-Tn5::luxKm2 transposon using mini-Tn7-lux elements that insert site-specifically at known genomic attachment sites and that can also be used to tag bacteria.